The epidemiology and type of injuries seen at the accident and emergency unit of a Nigerian referral center - Adoga, Adeyi A. (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: A plethora of injuries present at any accident and emergency unit, but the pattern of the injuries varies from region to region especially in ours with the increased ethno-religious clashes and terrorist attacks. This study aims to determine the epidemiology and type of injuries presenting to our center with the possibility of developing injury surveillance initiatives in our center and Nigeria as a whole. MATERIALS AND METHODS: Injured patients consecutively presenting to the accident and emergency department of the Jos University Teaching Hospital within the period February 2011 to January 2012 were prospectively recorded. RESULTS: A total of 720 injured patients admitted with an age range of 8 months to 75 years (mean = 37.9; SD = ±52.4), which consists of 544 males and 176 females giving a male to female ratio of 3.1:1. Patients aged 20-29 years were in the majority (n = 220, 30.6%) with peak incidences in the period of communal clashes. Injuries sustained from motorcycles were the highest (n = 248, 34.4%). Others were 160 (22.2%) in other vehicular and pedestrian injuries, machete (n = 128), gunshots (n = 92), burns (n = 36), bomb blast injuries (n = 16), fall from heights (n = 32) and miscellaneous (n = 8). Injuries sustained in communal clashes and terrorist attacks accounted for 236 (32.8%) presentations. The most common site of injury was the head (n = 30 4, 42.2%). Relatives, passersby and law enforcement agencies brought patients to the hospital with times between injury and presentation ranging from 1 h to 3 weeks. 40 (5.6%) patients were brought in dead. CONCLUSION: A collective effort - on the part of the government and the citizenry is required to ensure better outcomes and a safer society for all.